2008
DOI: 10.1111/j.1752-1688.2008.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dredging on Phosphorus Transport in Agricultural Drainage Ditches of the Atlantic Coastal Plain1

Abstract: Drainage ditches can be a key conduit of phosphorus (P) between agricultural soils of the Atlantic Coastal Plain and local surface waters, including the Chesapeake Bay. This study sought to quantify the effect of a common ditch management practice, sediment dredging, on fate of P in drainage ditches. Sediments from two drainage ditches that had been monitored for seven years and had similar characteristics (flow, P loadings, sediment properties) were sampled (0‐5 cm) after one of the ditches had been dredged, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Our finding that dredging lowered effluent P relative to the control when hydrology was held constant is consistent with Smith and Huang (2010) and Shigaki et al (2008). Disrupted materials from dredged and undredged ditches from the same site where our intact soil mesocosms were taken were compared for their P‐release potential by Shigaki et al (2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that dredging lowered effluent P relative to the control when hydrology was held constant is consistent with Smith and Huang (2010) and Shigaki et al (2008). Disrupted materials from dredged and undredged ditches from the same site where our intact soil mesocosms were taken were compared for their P‐release potential by Shigaki et al (2008).…”
Section: Discussionsupporting
confidence: 93%
“…In a field study of Midwestern collection ditches, Smith and Huang (2010) observed decreased P exports in dredged ditch reaches versus undredged reaches for up to 1 yr after dredging (similar to Shigaki et al, 2008, and the present study; Fig. 2b).…”
Section: Discussionsupporting
confidence: 90%
“…This can result in increased bank erosion (hence particulate P loss) and removal of bed materials with a high P sorption capacity leading to ditches becoming a P source rather than a P sink Sharpley et al, 2007;Smith and Pappas, 2007;Shigaki et al, 2008). In some instances, however, short-term increases in P retention have been observed following ditch dredging (Smith and Huang, 2010).…”
Section: Drainage Ditchesmentioning
confidence: 99%
“…Considerable research documents the role of drainage ditches as conduits of field pollutants (e.g., Kleinman et al 2007) and Figure 1 the effect of routine ditch maintenance practices such as dredging in disrupting the natural buffering ability of ditches Pappas and Smith 2007;Shigaki et al 2008). However, a growing body of research suggests the potential exists for using vegetated open ditches as best management practices for mitigating potential agricultural contaminants.…”
Section: Drainage Ditch Managementmentioning
confidence: 99%